First record of a Maastrichtian sauropod dinosaur from Egypt - Rauhut, Oliver W. M.; Werner, Christa (Bernard Price Institute for Palaeontological Research, 1997)
A left femur of a small sauropod dinosaur was found in the Maastrichtian part of the Ammonite Hill Member of the Dahkla Formation of southwestern Egypt. it represents the first dinosaur remains of certain Maastrichtian age from Egypt and the second record of dinosaurs from this stage within Africa. Moreover, the Egyptian specimen shows similarities to femora of brachiosaurids, possibly extending the temporal range of this family up to the very end of the Mesozoic.
Main article
Keywords: Africa, Maastrichtian, Dinosauria, Sauropoda, Brachiosauridae